Optical and Magnetic Response of Pure and CU-Ions Substituted Dysprosium Oxide Thin Films for Various Applications - Muhammad Tauseef Qureshi (East European Journal of Physics, 2023)
Dysprosium oxide (Dy2O3) and Cu/Dy2O3 thin films of thickness 117.14 nm and 258.30 nm, respectively were successfully deposited via a well-known DC-magnetron sputtering technique. Field emission scanning electron microscopy clarifies the growth of uniform and fine granular particles on silicon substrate. The hexagonal closed pack structure for both the thin films has been observed by the x-ray diffraction analysis and it was observed that by inclusion of copper the HCP structure of thin film was retain with a slight shift in the main peak. The reduction from 3.9 eV to 3.8 eV in the energy band gap value was observed by incorporation of copper ions Dy2O3 thin films. The M-H loops obtained through Vibrating Sample Magnetometer (VSM) shows that Dy2O3 thin film behave ferromagnetically at low temperature with a saturation magnetization value of 2860 emu/cc and evolves through its phase transition temperatures and behave paramagnetically at room temperature. In Cu/Dy2O3 case, the diamagnetic response of Cu dominates and produces reverse hysteresis loop at both temperatures make it a suitable candidate for energy and memory storage devices applications.